Role of delayed phase contrast-enhanced CT in the intra-thoracic staging of non-small cell lung cancer (NSCLC): What does it add?. Issue 144 (November 2021) - Larici, Anna Rita; Franchi, Paola; del Ciello, Annemilia; Sica, Giuliano; Coviello, Davide; De Waure, Chiara; Cicchetti, Giuseppe; Rovere, Giuseppe; Storto, Maria Luigia; Farchione, Alessandra; Calandriello, Lucio; D'Ambra, Giulia; et al.
Highlights: 60-second DEP ce-CT boosts radiologists' confidence level in NSCLC staging. 60-second DEP ce-CT improves recognition of tumour necrosis and nodal involvement. 60-second DEP ce-CT significantly changes the N stage determination. 60-second DEP ce-CT aids in excluding chest wall invasion and venous invasion. Abstract: Purpose: The aim of the study was to investigate differences in non-small cell lung cancer (NSCLC) intra-thoracic staging by using contrast-enhanced computed tomography (ce-CT) at the arterial phase (AP), at the arterial plus delayed phases (AP + DEP), and at the delayed phase (DEP), and to evaluate their potential impact on disease staging. Materials and methods: Two chest radiologists with different level of expertise and a general radiologist independently reviewed the chest CT exams of 150 patients with NSCLC; CT scans were performed 40 s (AP) and 60 s (DEP) after contrast material injection. Image assessment included three reading sessions: session A (AP), session B (AP + DEP) and session C (DEP). CT descriptors for the primary tumour (T), regional nodal involvement (N), and intra-thoracic metastases (M) were evaluated in each reading session. Readers had to assign a confidence level (CL) for the assessment of each descriptor and define the TNM stage. Friedman and Cochran Q test was used to compare the assessments of the 3 reading sessions; inter-reader agreement was determined (Intraclass Correlation Coefficient – ICC). Results: The CL was significantly higher in sessions B and C than in session A for all descriptors, with the exception of pulmonary arterial invasion. Primary tumour inner necrosis and regional nodal involvement were detected in a significantly higher number of cases in sessions B and C as compared to session A ( p ≤ 0.001). DEP significantly changed N stage determination ( p < 0.001), particularly N3, and excluded chest wall invasion ( p = 0.05) and venous invasion ( p = 0.001). The agreement was good among the 3 readers (ICC = 0.761) and excellent between the 2 chest radiologists (ICC ≥ 0.940), regardless of the contrast phase. Conclusions: The 60-second DEP ce-CT for staging NSCLC significantly increased the readers' CL, changed the N stage determination, and helped excluding chest wall invasion and venous invasion.